Political Ethics in Leadership: Impact of Behaviour Ethics Implementation of Regional Heads in Indonesia - Muhammad Iqbal Fadhlurrohman; Tengku Imam Syarifuddin; Etika Khairina (Journal of Government and Political Issues, 2021)
The focus of this research is to see how political ethics becomes an ideology for the creation of good behavior for a leader. Political ethics is a concept of morality that is very necessary for a leader or regional head in the political behavior that will be implemented. The political ethics of leaders or regional heads by prioritizing honesty, fairness, and responsibility has a very noble goal by prioritizing values and morality for the creation of good leadership and avoiding lousy behavior such as corruption which is very detrimental to many parties. This study using literature analysis seen from previous studies with data obtained from journals, news, websites, and also from internet data relating to the theme of this research. The results of this study stated that political ethics is needed for leaders or regional heads who aim to avoid making mistakes that make a loss and in this study look at the problem of regional heads or leaders in Indonesia whether political ethics is instilled in each of them so that the behavior of leaders or regional heads does not deviate from values and morality for the creation of good leadership. The concept of political ethics is the concept of action on the behavior of each person, especially a leader.